Understanding the role of forgiveness in shaping the flourishing of Hindu married couples - Priyanka Parihar; Gyanesh Tiwari; Pramod Kumar Rai (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2023)
Hindu Marriage is a sacrament that has been conceived to achieve a variety of worldly and spiritual goals. Some forms of hurt, untruthful or betrayal may involve a marriage relationship that may significantly impact the forgiveness behaviours of one or other members of married couples influencing their flourishing. The study examined the role of some biographic features, the forgiveness of self, others and situations in shaping the well-being of married Hindu couples. Employing a correlational design, the study recruited 300 married Hindu couples with the age ranging from 25 to 50 years by snowball sampling. Forgiveness and well-being were measured with the help of The Heartland Forgiveness Scale and Mental Health Continuum. The findings showed that education, age, domicile, occupation and years of marriage and the three types of forgiveness exhibited significant positive correlations with the indices of well-being whereas gender, number of children, nature of family (nuclear or joint), number of family members and socioeconomic status showed negative correlations with the same. Employment status and age emerged as the most significant predictors for hedonic and psychological well-being, respectively. Conversely, others' forgiveness did the same for social and eudaimonic well-being and flourishing. Indian socio-cultural conditions, the conceptualization of Hindu marriage and relevant earlier studies have been used to discuss the findings. Some biographic attributes, inclination towards a postmodern lifestyle and others' forgiveness seem to shape the well-being outcomes of married Hindu couples. Directions for future researchers have been discussed.